In-vitro Test of Biological Control by Trichoderma spp. Toward Ganoderma that attacked Sengon - Elis Nina Herliyana; Ratna Jamilah; Darmono Taniwiryono; Muhammad Alam Firmansyah (Jurnal Silvikultur Tropika, 2013)
Ganoderma infection, red root-rot fungi or basal stem rot disease is becoming more prevalent and causing significant loss in sengon (Falcataria moluccana) in Indonesia. Trichoderma spp. is the alternative choice in the biological control of Ganoderma sp The objectives of the research were to study the potential of biological agents antagonism Trichoderma harzianum and Trichoderma pseudoconingii against Ganoderma that attacked Sengon with in vitro method. Antagonism test of Trichoderma spp with co-culture method modification to five Ganoderma isolates on PDA medium was conducted in Forest Pathology Laboratory, IPB, Bogor. The potential biological agents for protecting Ganoderma spp. on sengon were T. harzianum strain DT38 and T. pseudoconingii DT39. The research results showed that the Trichoderma spp. inhibit growth of five Ganoderma isolates that were attacked sengon tree from Lampung (Ganoderma L12, L6, L3) and Kalimantan Selatan (K2, dan K1) between 11,7 – 48,8%.Keywords: Biological Control, Falcataria moluccana, Ganoderma sp., Trichoderma harzianum, Trichoderma pseudokoningii,